Rebel-in-chief : inside the bold and controversial presidency of George W. Bush - Barnes, Fred, 1943- (New York : Crown Forum, 2006)
Veteran political reporter Barnes provides an insider's view of how Bush's unique presidential style and bold reforms are dramatically remaking the country--and, indeed, the world. In the process, Barnes shows, the president is shaking up Washington and reshaping the conservative movement. Barnes has gained extraordinary access to the Bush administration, conducting rare one-on-one interviews with Bush, Cheney, Rice, Rumsfeld, and many other close presidential advisers. Barnes shows how Bush acts as an "insurgent force" in the nation's capital; how he is redefining conservatism for a new era; how he has revolutionized American foreign policy--and how his crusade for democracy would have been anathema to Bush himself only five years ago; when and why he decided to go into Iraq, even knowing that he was putting his future at risk; how he routinely defies conventional wisdom--and why he usually wins.--From publisher description.
The insurgent leader -- The outsider : Bush and the Washington establishment -- Strike the hole, strike the rancher : the Bush revolution in foreign policy -- Reversal : reinventing America's role in the Middle East -- Unflinching : bringing democracy to Iraq -- The crusade for democracy -- Taking ownership -- Faith-based -- The new conservatism -- The new majority.
Includes index.
Keywords: Bush, George W. -- 1946- -- Political and social views; Bush, George W. -- 1946- -- Influence; Conservatism -- United States; United States -- Politics and government -- 2001-2009.; United States -- Foreign relations -- 2001-